Fictitious (Implied) Administrative Acts: Prospects of Integration Into Russian Legislation - V. V. Maslov (Теоретическая и прикладная юриспруденция)
The article analyses the category of a ﬁctitious administrative act. It is pointed out that the term “ﬁctitious administrative act” borrowed from German administrative law is not appropriate for Russian law. As a substitute for it, another term is offered — “implied administrative act”. It is argued that the implied administrative act, being a legal ﬁction, is not an administrative act in the proper sense of the word. Consequently, although the rules on the invalidity of administrative acts may be applied to implied administrative acts, not all grounds of invalidity may be applicable to them. As a result of the analysis of foreign legislation, possible models of using of implied administrative act are presented. The paper demonstrates that the legislator can establish a positive or negative ﬁctitious conclusion either as a general rule or in relation to individual administrative procedures. The objectives of introducing the category in question into the legislation are also determined. The article shows that the goals of normative ﬁxation and the use of positive and negative ﬁctitious conclusion in legal practice are different. The purpose of a negative ﬁctitious conclusion is to eliminate the state of legal uncertainty in cases where challenging the inaction of an administrative body for one reason or another is difﬁcult. At the same time, a positive ﬁctitious conclusion generally leads to simpliﬁcation and acceleration of administrative procedures and contributes to procedural savings. Taking into account foreign experience, the paper concludes that it is advisable to introduce a positive implied administrative act into Russian legislation to simplify and speed up administrative procedures. General recommendations on possible ways of its introduction are given, in particular, it is indicated that it is unacceptable to establish such a condition as a general rule.